2017
DOI: 10.1080/07420528.2017.1411359
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of objectively measured bedtime and chronotype in US adolescents and adults: NHANES 2003–2006

Abstract: The proposed measures, OBT-D and OBT-M, provide useful information of time in bed and chronotype in NHANES 2003-2006. They identify within-week patterns of bedtime and can be used to study associations between the bedtime and the large number of health outcomes collected in NHANES 2003-2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…The average weekend sleep duration of 8.59 hours closely matches sleep durations from other studies based on self-reported data (Liu et al 2012;Rutters et al 2014;Fischer et al 2017;Koopman et al 2017) , which commonly overestimates sleep duration compared to objective measures such as actigraphy (Lauderdale et al 2006;Silva et al 2007;Arora et al 2013;Dietch et al 2017) . Well-established trends in both objective and subjective sleep analyses demonstrate whites sleep upwards of 45 minutes longer than blacks (Lauderdale et al 2006;Dietch et al 2017) , and women sleep upwards of 30 minutes longer than men (Lauderdale et al 2006;Liu et al 2012;Dietch et al 2017;Urbanek et al 2017) , which are all consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The average weekend sleep duration of 8.59 hours closely matches sleep durations from other studies based on self-reported data (Liu et al 2012;Rutters et al 2014;Fischer et al 2017;Koopman et al 2017) , which commonly overestimates sleep duration compared to objective measures such as actigraphy (Lauderdale et al 2006;Silva et al 2007;Arora et al 2013;Dietch et al 2017) . Well-established trends in both objective and subjective sleep analyses demonstrate whites sleep upwards of 45 minutes longer than blacks (Lauderdale et al 2006;Dietch et al 2017) , and women sleep upwards of 30 minutes longer than men (Lauderdale et al 2006;Liu et al 2012;Dietch et al 2017;Urbanek et al 2017) , which are all consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…These patterns are consistent with expected constraints of working-age adults and altered sleep requirements in the elderly, and have been observed previously (Ohayon et al 2004;Silva et al 2007;Hashizaki et al 2015) . Both sleep midpoint and sleep lag also vary as a function of age, which has been observed in adolescents and young adults (Rutters et al 2014;Hashizaki et al 2015;Fischer et al 2017;Koopman et al 2017;Urbanek et al 2017) . Gender and race did not explain social sleep lag, which may reflect broader cultural norms and chronotype shifts in younger individuals regardless of background.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, for the second sensitivity analysis, valid day was defined as a day with wear time between 10 and 20 hours. The threshold of 20 hours has been previously used to identify “bed-time” periods in NHANES [52]. After exclusion of invalid subject-days from the original samples, 3362 (with 534 deaths) subjects remained and same Cox PH models where re-estimated.…”
Section: Resultsmentioning
confidence: 99%
“…The dim light melatonin onset (DLMO) is the gold standard objective method of detecting circadian phase in humans 34 . Objectively measured bedtime duration and midpoint of the bedtime have been shown to give useful information of chronotype 35 . However, shortened versions of MEQ have been shown to be reliable and are widely used in epidemiological studies 23,24,36 …”
Section: Discussionmentioning
confidence: 99%